Numerical analysis on an OOK-NRZ visible light communication system based on a single white LED - 贾永坡 叶玮琳 田崇文 全相印 王嘉琪 宋占伟 郑传涛 (Optoelectronics letters, 2011)
An OOK-NRZ visible light communication （VLC） system is designed by using a single white LED and a 550 nm visible photodetector. The emitting model of the single LED is established, and the general expression of the detector＇s output signals under OOK modulation is deduced. With the selected LED, detector and other related parameters, the designed communication system is optimized and its performance is analyzed. The optimized communication distance between the LED and the detector is 0.54 m at the communication bit rate of 1 Mbit/s. With the best communication distance, when the signal-to-noise ratio （SNR） is larger than 6.5 dB, the bit error rate （BER） can drop to 10^-4. The analytical model and theory presented in this paper can be of certain practical meanings in the design of similar communication systems.